Over 20-year Follow-up Result of Total Knee Arthroplasty for Knee Arthropathy: A Single Center Cohort Study - XU Yiming; HU Mingwei; ZHU Wei; YU Muyang; LIN Jin; JIN Jin; QIAN Wenwei; FENG Bin; WENG Xisheng (Xiehe Yixue Zazhi)
ObjectiveTo evaluate long-term survival and clinical outcomes of patients with knee osteo-arthritis undergoing total knee arthroplasty (TKA) through long-term follow-up.MethodsThis study was based on a previous cohort study that had completed follow-up. We retrospectively collected clinical data of patients with knee arthropathy (including knee osteoarthritis and knee rheumatoid arthritis) who received the first TKA operation in Peking Union Medical College Hospital from 1993 to 2002 and were followed up for more than 20 years, and conducted a unified follow-up on them in November 10, 2024 (the last follow-up). Kaplan-Meier curve was used to evaluate the survival rate. Hospitals for special surgery (HSS) scores and joint range of motion (ROM) were compared before surgery, 10 years after surgery and at the last follow-up to evaluate the clinical efficacy of TKA. Likert scale was used to evaluate patient satisfaction at the last follow-up.ResultsA total of 226 patients (246 knees) received their first TKA in Peking Union Medical College Hospital from 1993 to 2002 and were followed up for more than 10 years. Among them, 104 patients (131 knees) were included in the study at the last follow-up, including 21 patients (24 knees) with prosthesis in place, 18 patients (18 knees) who underwent reoperation for various reasons, and 65 patients (89 knees) who died from non-TKA surgical causes. Up to the last follow-up, there were 29 patients (35 knees) with an average follow-up of more than 20 years, and 12 patients (16 knees) completed HSS score, ROM measurement and patient satisfaction evaluation. Kaplan-Meier curve showed that the 10-year, 15-year, 20-year, and 25-year survival rates were 93.6%, 92.4%, 89.8%, and 71.8%, respectively. The HSS score at the last follow-up was lower than that at 10- year postoperative follow-up[(84.69±11.03) scores vs. (95.25±13.32) scores, P < 0.05], but significantly improved compared with the preoperative[(84.69±11.03) scores vs. (58.75±7.19) scores, P < 0.05]. The ROM of knee joint were (93.44±17.30) °, (101.88±13.33) °, and (91.56±15.98) ° at preoperative, 10-year of postoperative and last follow-up, respectively, and there was no statistical significance between the groups (P > 0.05). In terms of patient satisfaction, the 10 knees (62.50%) scored 4 points (very satisfied), the remaining 6 knees (37.50%) scored 3 points (satisfied), and the satisfaction rate was 100%.ConclusionTKA treatment for knee arthropathy has high long-term prosthesis survival rate, significant improvement of knee joint function and high patient satisfaction.